Qualitative representation of spatio-temporal knowledge. (December 2018) - Della Penna, Giuseppe; Orefice, Sergio
Abstract: In this paper we present PCT ( Position-Connection-Time ), a formalism capable of representing spatio-temporal knowledge in a qualitative fashion. This framework achieves an expressive power comparable to other classic spatial relation formalisms describing common topological and directional spatial relations. In addition, PCT introduces new classes of relations based both on the position of the objects and on their interconnections, and incorporates the notion of time within spatial relations in order to describe dynamic contexts. In this way, PCT is also able to model spatial arrangements that change over time, e.g., moving objects.